AB1392 Predictors of work impairment in a randomized controlled trial of etanercept-methotrexate therapy in patients with moderate rheumatoid arthritis. (23rd January 2014) - Strand, V.; Jones, T.V.; Li, W.; Koenig, A.S.; Kotak, S.
Abstract : Background: In patients (pts) with rheumatoid arthritis (RA), work disability is a major consequence of reduced physical function, which can occur with active joint inflammation and joint damage. 1, 2 In a recent multinational database study, work disability was reported in more than one third of pts working at the time of RA symptom onset. 2 A 2006 systematic review indicated that 66% of employed RA pts experienced productivity loss due to RA in the prior year. 3 Expenditures related to lost productivity exceed direct expenditures in determining overall RA costs. 4 Despite increased use of very effective non-biologic and biologic therapies in RA, work disability remains common, prompting further investigation into the relationships among work disability, disease activity, and other variables. Objectives: To examine factors predicting impairment in work productivity in pts with moderately active RA enrolled in the randomized, double-blind period of the PRESERVE trial. Methods: Pts with 3.2<DAS28≤5.1 who achieved DAS28 low disease activity (DAS28 ≤3.2, avg wk 12–36 + at wk 36) after 36 wks of open-label treatment with etanercept (ETN) 50 mg QW + methotrexate (MTX; E50/M) were randomized to double-blind treatment with E50/M (n=202), ETN 25 mg QW + MTX (E25/M; n=202), or placebo + MTX (P/M; n=200) for 52 wks. Work productivity was assessed using the Work Productivity Activity Impairment Questionnaire: Rheumatoid Arthritis (WPAI:RA) at baseline (BL) and after double-blind treatment (wk 88). Correlation (Pearson's r) and linear regression analyses were performed using the WPAI:RA % of overall work impairment as the dependent variable and BL age, gender, duration of RA (wk 36), Health Assessment Questionnaire (HAQ) score ≤0.5 vs >0.5 (wk 36), pt global assessment (PGA) of disease activity (0–10; wk 36), WPAI:RA score (wk 36), and treatment as independent variables. Results: Pts' age and gender and the PGA of disease activity at baseline were not significantly associated with % overall work impairment at wk 88 (table ). In contrast, RA duration, HAQ score >0.5, and WPAI:RA scores at BL were all significantly predictive of work impairment (p<0.05). Controlling for other factors, treatment with E50/M was significantly better than P/M in lessening impairment of work productivity at wk 88 (p<0.05), whereas E25/M was not. Conclusions: Disease duration, HAQ score >0.5, and work impairment at baseline were significant predictors of continuing work impairment in pts with moderate RA enrolled in the PRESERVE trial. After controlling for other factors, pts receiving etanercept 50 mg plus methotrexate reported significant improvement in the overall percentage of work impairment compared with pts receiving placebo plus methotrexate. References: Verstappen SMM, et al. Arthritis Rheum. 2004;51:488–97. Sokka T, et al. Arthritis Res Ther. 2010;12:R42. Burton W, et al. Occup Med. 2006;56:18–27. Ruof J, et al. Ann Rheum Dis. 2003;62:544–50. Disclosure of Interest: V. Strand Consultant for: Amgen, Pfizer Inc, T. Jones Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, W. Li Employee of: Pfizer Inc, A. Koenig Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Kotak Shareholder of: Pfizer Inc, Employee of: Pfizer Inc